2022
DOI: 10.1039/d1cc06756g
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of dihydro-1,4-benzothiazine derivatives via oxidative ring-expansion of 2-aminobenzothiazoles with olefins

Abstract: A concise and efficient approach to prepare dihydro-1,4-benzothiazine derivatives is described via oxidative ring-expansion of 2-aminobenzothiazoles with olefins under metal-free conditions. This protocol is applicable for a wide range of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This is a novel synthetic method to generate various 1,4-benzothiazine six-membered-ring derivatives via the ring-opening of 2-substituted benzothiazole; for example, Bao et al reported the facile preparation of dihydro-1,4-benzothiazine derivatives via the oxidative ring-openingrecombination of 2-aminobenzothiazoles with olefins. [6] Quast developed a ring extension reaction of sulfonyl azide with a benzothiazole salt to yield 1,4benzothiazine derivatives (Scheme 1a). [7] Hachem previously reported a convenient method for synthesizing dihydrobenzothiazole compounds by reacting 2-aminothiophenol with 2, 5-dihydro-2, 5-dimethoxyfuran.…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel synthetic method to generate various 1,4-benzothiazine six-membered-ring derivatives via the ring-opening of 2-substituted benzothiazole; for example, Bao et al reported the facile preparation of dihydro-1,4-benzothiazine derivatives via the oxidative ring-openingrecombination of 2-aminobenzothiazoles with olefins. [6] Quast developed a ring extension reaction of sulfonyl azide with a benzothiazole salt to yield 1,4benzothiazine derivatives (Scheme 1a). [7] Hachem previously reported a convenient method for synthesizing dihydrobenzothiazole compounds by reacting 2-aminothiophenol with 2, 5-dihydro-2, 5-dimethoxyfuran.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of 2-aminobenzothiazoles are reported to have diverse biological activities like cytotoxicity, antiinfammatory, analgesic, anthelmintic, antiviral, antidiabetic, antimicrobial, antileishmanial, anticonvulsant, Alzheimer's disease, and calcium channel blocking [3][4][5][6]. Te present study was carried out on 6-sulfonamide containing 2-aminobenzothiazole Schif bases derivatives as lead molecules of the study with the aid of docking for evaluating their diuretic activity, which is an adjutant therapy in treating hypertension [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Benzyl alcohol 8 was also isolated in 75% yield via the oxidation 13 of the hydroboration 15 product from 3a . Furthermore, we successfully realized the preparation of the dihydro-1,4-benzothiazine compound 10 in 69% yield via oxidative ring-expansion 16 of 2-aminobenzothiazoles 9 with 3a .…”
mentioning
confidence: 99%